Usability evaluation of navigation tasks by people with intellectual disabilities: a Google and SAPO comparative study regarding different interaction modalities - Rocha, Tania (2017)
This paper presents a case study regarding the usability evaluation of navigation tasks by people with intellectual disabilities. The aim was to investigate the factors affecting usability, by comparing their user-Web interactions and underline the difficulties observed. For that purpose, two distinct study phases were performed: the first consisted in comparing interaction using two different search engines' layouts (Google and SAPO) and the second phase consisted in a preliminary evaluation to analyze how users performed the tasks with the usual input devices (keyboard and mouse) and provide an alternative interface to help overcome possible interaction problems and enhance autonomy. For the latter, we compared two different interfaces: a WIMP-based one and speech-based one. The main results obtained showed that users had a better performance with Google (with a simpler layout) than with SAPO (with a complex layout), and despite displaying a good keyboard handling ability, they did not show autonomy using this input device (due to the need for reading/writing when handling this device). In this perspective, Google's speech recognition application could indeed be considered an alternative for interaction. However, we found that the speech recognition interface is not as robust as it should be: it could be more precise and less prone to errors due to poor word pronunciation. After this two-phased study, we think we may be able to infer some recommendations to be used by developers in order to create more intuitive layouts for easy navigation regarding this group of people, and thereby facilitate digital inclusion.